2018
DOI: 10.3390/insects9010019
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Species Diversity of Rice Hopper Parasitoids in Southeast Asia

Abstract: Ongoing intensification of rice production systems in Southeast Asia is causing devastating yield losses each year due to rice hoppers. Their continuing development of immunity to resistant rice varieties and pesticide applications further complicates this problem. Hence, there is a high demand for biological control agents of rice hoppers. Egg parasitoid wasps are among the most important natural enemies of rice hoppers, such as Nilaparvata lugens and Nephotettix spp. However, our knowledge of their diversity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…(Trichogrammatidae) that we did not detect among parasitized eggs. Furthermore, Sann et al (2018) [ 71 ] have shown that the diversity of Anagrus and Gonatocerus species that parasitize BPH and GLH (and presumably WBPH) in the Philippines is underestimated because of the occurrence of several cryptic species. Because the results from sentinel plants are directly related to parasitoid function, our results indicate that egg parasitism by Oligosita spp.…”
Section: Discussionmentioning
confidence: 99%
“…(Trichogrammatidae) that we did not detect among parasitized eggs. Furthermore, Sann et al (2018) [ 71 ] have shown that the diversity of Anagrus and Gonatocerus species that parasitize BPH and GLH (and presumably WBPH) in the Philippines is underestimated because of the occurrence of several cryptic species. Because the results from sentinel plants are directly related to parasitoid function, our results indicate that egg parasitism by Oligosita spp.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has been conducted on the diversity of parasitoids in rice fields using molecular identification methods. Existing studies primarily rely on the first-generation sequencing of the COI gene to identify a small subset of parasitoids [20]. However, there is much less research focusing on the diversity of parasitoids in rice fields utilizing highthroughput second-generation sequencing via metabarcoding technology.…”
Section: Introductionmentioning
confidence: 99%